Prophecy In Later Islamic Thought: The Mystical Views of Shah Waliyyullah Ad-Dihlawi - Syamsuddin Arif (TSAQAFAH, 2009)
Scholarly interest in the thought and teachings of Shâh Waliyyullâh adDihlawî has increased in recent years –not surprisingly, given the richness and profundity of his writings. This article explores the mystical dimension of prophecy emerging from Shâh Waliyyullâh’s insights and remarks, focusing on the key concepts such as the World of Images (‘Âlam al-Mithâl), the Highest Council of Angels (al-Mala’ al-A‘lâ) and the Holy Enclave (Haz} îrat al-Quds), which help explain how, from the sûfî point of view, prophecy is possible. The main task of a prophet is to set up order in social, political and economic life of people. The prophet receives revelation which enables him to communicate the Divine Message to mankind containing all that is necessary for their welfare both in this life and the next according to the Divine Plan.